Gain-of-function research and model organisms in biology - Evans, Nicholas G. (Journal of medical ethics, 2024)
So-called ‘gain-of-function’ (GOF) research is virological research that results in a virus substantially more virulent or transmissible than its wild antecedent. GOF research has been subject to ethical analysis in the past, but the methods of GOF research have to date been underexamined by philosophers in these analyses. Here, we examine the typical animal used in influenza GOF experiments, the ferret, and show how despite its longstanding use, it does not easily satisfy the desirable criteria for an animal model. We then discuss the limitations of the ferret model, and how those epistemic limitations bear on ethical and policy questions around the risks and benefits of GOF research. We conclude with a reflection on how philosophy of science can contribute to ethical and policy debates around the risks, benefits and relative priority of life sciences research.